Density, Viscosity, Vapor-Liquid Equilibrium, Excess Molar Enthalpy and IR Spectrocopy of [Chloroform+Di-isopropyl Ether (DIPE)] - Gómez Marigliano, Ana Clelia (2015)
Density, viscosity and refractive index measurements in the T=[288.15 to 303.15] K range of pure chloroform and di-isopropyl ether, as well as of the binary system [x1 chloroform+(1-x1) di-isopropyl ether (DIPE)] over the whole concentration range at T=298.15 K were made. The experimental results for the pure components were fitted to empirical equations. Calculated values are in agreement with the experimental ones. Data of the binary mixture were further used to calculate the excess molar volume, refractive index deviations and viscosity deviations. Excess molar enthalpy at T=(298 ±1) K and vapor-liquid equilibrium measurements at T=(313.15 ±0.05) K were also measured for the binary system. Activity coefficients and the excess molar Gibbs energy are calculated. This binary system shows strong negative deviations from ideality and exhibits a minimum pressure azeotrope, whose coordinates are: P=(32.90 ± 0.05) kPa and x1=(0.402 ±0.002). Excess and deviation properties were fitted to the Redlich-Kister polynomial relation.The optimized structures and vibrational frequencies for DIPE, chloroform and their 1:1 complex were calculated by means of density functional theory (DFT) techniques using the B3LYP functional combined with the 6-31G(d,p) basis set.Raman and FT-infrared spectra of pure chloroform (1) and DIPE (2), as well as of the binary system were recorded.The recorded Raman and FTIR spectra confirm the existence of these type of hydrogen-bonded complexes. The ideal associated solution model was used to calculate the equilibrium constants, which compares well with results obtained from spectroscopic data and the enthalpy of formation of the hydrogen bond.